2017
DOI: 10.3389/fneur.2017.00701
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography in Alzheimer’s Disease and Other Neurodegenerative Diseases

Abstract: Over the past decade, a surge of evidence has documented various pathological processes in the retina of patients suffering from mild cognitive impairment, Alzheimer’s disease (AD), Parkinson’s disease (PD), and other neurodegenerative diseases. Numerous studies have shown that the retina, a central nervous system tissue formed as a developmental outgrowth of the brain, is profoundly affected by AD. Harboring the earliest detectable disease-specific signs, amyloid β-protein (Aβ) plaques, the retina of AD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(121 citation statements)
references
References 159 publications
(235 reference statements)
5
113
1
2
Order By: Relevance
“…Furthermore, to emphasize the clinical relevance of this technique, it was designed to be used with widely available clinical imaging devices (Ehler et al, 2015). It has recently been proposed that OCT may be used in various neurodegenerative diseases, due to its capability in measuring volumetric changes of the retina (Doustar et al, 2017). However, given the nature of neurodegenerative diseases, it is paramount that the diagnosis is established at the earliest possible time-point to provide the best prognosis to the patient.…”
Section: Rhodopsin Quantification and Scanning Laser Ophthalmoscopymentioning
confidence: 99%
“…Furthermore, to emphasize the clinical relevance of this technique, it was designed to be used with widely available clinical imaging devices (Ehler et al, 2015). It has recently been proposed that OCT may be used in various neurodegenerative diseases, due to its capability in measuring volumetric changes of the retina (Doustar et al, 2017). However, given the nature of neurodegenerative diseases, it is paramount that the diagnosis is established at the earliest possible time-point to provide the best prognosis to the patient.…”
Section: Rhodopsin Quantification and Scanning Laser Ophthalmoscopymentioning
confidence: 99%
“…Prominent visual deficits including contrast sensitivity and poor visual memory performance have been reported in AD patients years before clinical diagnosis, with increasing evidence of pathology at several levels of the visual pathway (Gao et al, 2015). Optical coherence tomography (OCT) has emerged as a non-invasive and readily available approach to observe changes in retinal structure, providing high-resolution cross-sectional images of the macula, and retinal nerve fiber layer (RNFL) (Cheung et al, 2017;Doustar et al, 2017). The RNFL is formed by retinal ganglion cells axons and represents the innermost layer of the retina.…”
Section: Introductionmentioning
confidence: 99%
“…Recent neuroimaging studies reveal a decreased volume in the olfactory regions of the brain, while neuropathological studies found a high accumulation of α-synuclein, αβ amyloid, and Tau proteins in the olfactory bulb during the early stages of neurodegenerative diseases [47,48]. Something similar can be seen in the optical pathways as well, as there is an increase of visual hallucinations, reduced color recognition, visual acuity problems, and double vision as neurodegeneration progresses [49]. Pain syndromes are frequent as well and are more likely of neuropathic origin.…”
Section: Nonmotor Symptoms In Neurodegenerative Diseasesmentioning
confidence: 99%